Война нервов: роман / Михаил Нестеров - Нестеров Михаил Петрович (Спецназ ГРУ, 2006)
Экземпляры: ф.6 (20161017) / Инвентарный номер: 1847 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 56 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44